2019
DOI: 10.3390/coatings9080488
|View full text |Cite
|
Sign up to set email alerts
|

Paint Removal on the 5A06 Aluminum Alloy Using a Continuous Wave Fiber Laser

Abstract: Paint removal is an important part of ship and marine engineering ship processing. Aluminum alloy is extremely vital in the field of shipbuilding, due to its high strength and strong corrosion resistance ability. Therefore, the cleaning quality of aluminum alloy is a key factor in the service life of the ship. In this paper, the research about continuous wave (CW) laser cleaning technique is employed to clean the paint on the substrate of aluminum alloy. The track width and depth of laser ablated craters are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The thermal stress produced during the expansion process is stronger than the chemical bond or van der Waals force between the materials and exceeds the adhesion force between the oxide film or paint layer and the substrate. Consequently, the oxide film or paint layer can be peeled off from the surface of the substrate [ 46 , 47 ]. In addition, when the laser beam travels through the oxide film or paint layer and eventually reaches the substrate surface, a portion of it is reflected.…”
Section: The Mechanism Of Laser Cleaningmentioning
confidence: 99%
“…The thermal stress produced during the expansion process is stronger than the chemical bond or van der Waals force between the materials and exceeds the adhesion force between the oxide film or paint layer and the substrate. Consequently, the oxide film or paint layer can be peeled off from the surface of the substrate [ 46 , 47 ]. In addition, when the laser beam travels through the oxide film or paint layer and eventually reaches the substrate surface, a portion of it is reflected.…”
Section: The Mechanism Of Laser Cleaningmentioning
confidence: 99%
“…Lu et al used CW laser cleaning technology to clean paint from the surface of aluminum alloy substrates. By analyzing the surface morphology of the substrate after laser cleaning, it was found that when the laser power density is 11.9 W/cm 2 , the performance of the substrate after laser cleaning has better corrosion resistance and surface roughness [11]. Penide et al used a CW laser to remove graffiti from a stone surface and found that the CW mode has a better cleaning effect than the modulated wave mode.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be emphasized here that any increase in laser fluence beyond a threshold might trigger a risk of damaging the substrate. For instance, such an upper bound in terms of laser fluence was reported to be about11.9 W/cm 2 , which induces the excessive ablation of the substrate [31][32][33]. Together with experimental investigations, numerical simulations have also been extensively carried out to understand the underlying mechanism involved in laser cleaning.…”
Section: Introductionmentioning
confidence: 99%